The Early Days of Commercial FT-IR Spectrometry: A Personal Perspective. Issue 3 (March 2017) - Griffiths, Peter R.
The development of Fourier transform infrared (FT-IR) spectrometers in the mid-1960s followed along three lines. Interferometers for far-infrared FT spectrometry typically had a slow scan speed and the beam of radiation was modulated by a rotating chopper. Several instruments based on this system were developed commercially. Very high-resolution near-infrared FT spectrometers were based on cats-eye retroreflectors mounted in a step-scan interferometer; the beam of radiation was usually modulated by dithering one of the cats-eyes (phase modulation). No commercial instruments based on this principle were developed. In the third type of FT spectrometer, the beam was modulated by rapidly scanning one of the mirrors of a Michelson interferometer. While the early instruments based on this principle only gave rise to low-resolution spectra, the incorporation of laser fringe referencing at the end of the decade led to instruments that were the fore-runners of contemporary FT-IR spectrometers. In this article, the author's experiences with instruments of the first and third category are described.